From metaphysical representations to aesthetic life : toward the encounter with the other in the perspective of Daoism - Lacertosa, Massimiliano, 1980- (State University of New York Press, 2023)
Reevaluates Western and Chinese philosophical traditions to question the boundaries of entrenched conceptual frameworks.
Keywords: Taoist philosophy.; Philosophy, Chinese.; Aesthetics.; Philosophie taoïste.; Philosophie chinoise.; PHILOSOPHY / Taoist.; Aesthetics; Philosophy, Chinese; Taoist philosophy